Report of patients with chronic myeloid leukemia Kidwai Memorial Institute of Oncology, Bangalore over 15 years - Govind Babu (Indian Journal of Medical and Paediatric Oncology)
Kidwai Memorial Institute of Bangalore is one of the most comprehensive and major regional cancer center. It was established in 1974 and caters population not only from Karnataka, but also from Tamil Nadu, Andhra Pradesh. They presented the data of 540 patients out of which 95% patients were in chronic phase. Complete hematological response was seen in 98.45 of patients. Overall survival at 5 years was 86.5%.101 patients has suboptimal response were considered for and underwent mutational analysis, out of which 27 patients showed various mutations and are mentioned elaborately in the article.